Identification of Problems Faced in Road Maintenance (International Journal of Innovative Research in Engineering & Management, 2023)
A country's need for well-maintained road  networks and appropriate road maintenance procedures is  crucial for facilitating socioeconomic progress. However,  the majority of federal highways are not in excellent shape,  and more than one-third of them are in extremely poor or  poor condition, which makes them unsafe for driving. The  focus of this study was on identifying the current issues  with road maintenance and evaluating the overall  consequences of inadequate road maintenance on road  function. The preservation of the investment made in the  highway system as well as the comfort and safety of the  road user were found to depend heavily on the proper  design, routine inspection, and maintenance of the  drainage system.. All different kinds of distresses have  been categorized. For varying degrees of each suffering,  there are several causes and treatments. It is crucial to  recognize and fix the flaws in the current highway  maintenance procedures and system. In this study,  impacting factors such as cracks and cracking patterns,  roughness, rut depth, potholes, and deflections were taken  into account. The severity levels of the aforementioned  factors have been used to categorize them. Therefore, it is  advised that when doing any road maintenance, all  concerned parties pay full attention to the most severe  (acknowledged) issues in order to address the issues and  lessen their impacts.
Keywords: Road development plans; Effects; Problems; Road Maintenance